1999
DOI: 10.1161/01.cir.100.4.381
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Gain Predicts Blood Pressure Recovery During Simulated Ventricular Tachycardia in Humans

Abstract: Background-Despite similar degrees of left ventricular dysfunction and similar tachycardia or pacing rate, blood pressure (BP) response and symptoms vary greatly among patients. Sympathetic nerve activity (SNA) increases during sustained ventricular tachycardia (VT), and the magnitude of this sympathoexcitatory response appears to contribute to the net hemodynamic outcome. We hypothesize that the magnitude of sympathoexcitation and thus arterial baroreflex gain is an important determinant of the hemodynamic ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 21 publications
5
40
0
Order By: Relevance
“…He found that the arterial baroreflexes played a predominant role in modulating sympathetic activity and supporting arterial pressure, whereas cardiopulmonary baroreceptors played only a modest modulatory role in these responses [6]. We have found similar results in patients subjected to rapid pacing [5,7]. During invasive electrophysiologic testing, rapid ventricular pacing resulted in a state of sympathoexcitation despite the increase in cardiac filling pressures.…”
Section: Previous Studiessupporting
confidence: 71%
“…He found that the arterial baroreflexes played a predominant role in modulating sympathetic activity and supporting arterial pressure, whereas cardiopulmonary baroreceptors played only a modest modulatory role in these responses [6]. We have found similar results in patients subjected to rapid pacing [5,7]. During invasive electrophysiologic testing, rapid ventricular pacing resulted in a state of sympathoexcitation despite the increase in cardiac filling pressures.…”
Section: Previous Studiessupporting
confidence: 71%
“…Efferent post-ganglionic muscle SNA was recorded from the right peroneal nerve as previously described. 8,9 Briefly, a sterile microelectrode was inserted into a fascicle of the peroneal nerve near the fibular head. The nerve signals were amplified, filtered (700 to 2000 Hz), rectified, and discriminated.…”
Section: Measurementsmentioning
confidence: 99%
“…1997). The studies published so far have shown that the greater sensitivity of baroreceptor reflexes is associated with better tolerance of ventricular tachycardia (Hamdan et al 1999). Poor ventricular tachycardia tolerance may be related to inadequate stimulation of the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%